A cross-cultural scoping review of loneliness among international students - Bayot, Asher Escaño; Cerezo, Loraine (Journal of International Students, 2026)
This scoping review maps the cultural landscape of research on loneliness among international students. Drawing from 60 studies, including peer-reviewed articles and gray-literature sources, the review examines the cultural distribution of host contexts, patterns of cultural alignment between students’ home and host societies, the extent to which international students are analytically differentiated from each other and with domestic peers, and how cultural frameworks are used to conceptualize loneliness. The findings reveal a strong concentration of studies in Western and individualistic contexts, a limited number of international–domestic comparisons, and a predominant tendency to treat international students as a homogeneous group despite diverse cultural origins. In addition, while culture is frequently acknowledged as relevant, explicit theoretical engagement with cultural frameworks remains uneven.